The Creative Process in the Instrumental Karawitan “Biang Kerok” - I Putu Dony Suryawan (Journal of Aesthetics, Creativity and Art Management, 2026)
"Biang Kerok" was created using traditional musical instruments consisting of two Gender Wayang in slendro tuning and two Gender Rambat Semara Pegulingan Saih Pitu in pelog tuning. The choice of these different yet similar instruments aims to combine different tunings. The combination of these two different tunings is the key to this work, where the combination of pelog and slendro tunings produces previously unheard notes and creates new variations in timbre. During the creative process and stages, the composer combined the "Musical Composition Method" method, an article entitled "Karya Karawitan Baru Manikam Nusantara” (New Karawitan Works of Manikam Nusantara", and the "Panca Sthiti Ngawi Sani" method. This combination of several methods is crucial because it is closely related to the process of realizing this work. "Biang Kerok" is divided into three parts, each with a different textual and contextual focus, and is always directed by the composer's idea.